2020
DOI: 10.15386/mpr-1311
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pain levels in patients treated with 3 different orthodontic appliances - a randomized trial

Abstract: Background and aims. To compare pain levels experienced during initial alignment with three different orthodontic appliance types and to correlate pain with male and female differences, if any. Methods. A prospective, randomized 3- arm parallel trial allocated 36 adult orthodontic patients into three appliance groups: MBT 0.022” slot (Mini Twin, Ormco, Glendora, USA), self ligating 0.022" slot Damon 3MX (Ormco, Glendora, USA) and clear aligners (Smile align, Mumbai, India). The level of discomfort was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 32 publications
3
20
0
Order By: Relevance
“…The differences found in other studies [ 45 , 55 ] may be due to the heterogeneity in their samples (large skeletal discrepancies, different types of malocclusions, etc.). With this study, we tried to homogenize the patients in the four treatment groups in terms of number, type, and degree of malocclusion and by not including treatment with extractions or surgical cases.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The differences found in other studies [ 45 , 55 ] may be due to the heterogeneity in their samples (large skeletal discrepancies, different types of malocclusions, etc.). With this study, we tried to homogenize the patients in the four treatment groups in terms of number, type, and degree of malocclusion and by not including treatment with extractions or surgical cases.…”
Section: Discussionmentioning
confidence: 76%
“…Patients wearing aligners were found to have less pain, less discomfort during chewing, and less impact on social and psychological disability during the first week of analysis compared with those with conventional or low-friction braces. No statistically significant differences in pronunciation were found [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, previous studies reported positive changes and high satisfaction with Invisalign treatment especially with eating, chewing and appearance 19,36,37 . Invisalign treatment was associated with better satisfaction, better oral health related quality of life, and less negative impacts on oral health than fixed orthodontics [12][13][14][15][16]19,20,37,38 . They were associated with less disruption to eating and chewing and were rated as more satisfactory than fixed appliances 16 .…”
Section: Discussionmentioning
confidence: 92%
“…Invisalign treatment was associated with better satisfaction, better oral health related quality of life, and less negative impacts on oral health than fixed orthodontics [12][13][14][15][16]19,20,37,38 . They were associated with less disruption to eating and chewing and were rated as more satisfactory than fixed appliances 16 . Also, oral health related quality of life was not significantly affected by Invisalign treatment 38 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation